Germination and seedling establishment of Norway spruce (Picea abies) after clear-cutting is affected by timing of soil scarification. Issue 2 (March 2018) - Fløistad, Inger; Hylen, Gro; Hanssen, Kjersti; Granhus, Aksel
Abstract Natural regeneration of Norway spruce (Picea abies (L.) Karst.) is a relatively common practice in Norway on medium to low site indices. However, seedling establishment is often hampered by rapid regrowth of competing vegetation in scarified patches. The aim of our study was to examine the effect of coordinating scarification towards an expected seed-fall, by studying germination and seedling establishment in scarified patches of different age (fresh, one- and two-year-old). The experiment was conducted in two stands in southeast Norway that were clear-cut in 2007. Scarification was applied to subplots in autumn 2008–2010. To simulate seed-fall, seeds were sown in fresh scarification patches in spring 2009–2011, in one-year-old patches in 2010 and 2011, and in two-year-old patches in 2011. Both germination and seedling survival were negatively affected by the age of the scarified patches. Germination was higher, and mortality lower, at the small fern woodland site, compared with the bilberry woodland site. Sowing in fresh patches also resulted in increased height and root collar diameter of the seedlings compared with sowing in older patches. It is likely that the competing vegetation both on the site and in the scarification patches affected the growth of the seedlings. In conclusion, the age of the scarified patches affected both germination and mortality, as well as early growth of the seedlings.